2023
DOI: 10.3390/ijms242216248
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Assessment of Skin Surface Proteins of Psoriasis Vulgaris Patients in Response to Biological Therapy

Kadri Orro,
Kristiina Salk,
Anna Merkulova
et al.

Abstract: Measurements of skin surface biomarkers have enormous value for the detailed assessment of skin conditions, both for clinical application and in skin care. The main goals of the current study were to assess whether expression patterns of skin surface hBD-1, hBD-2, IL-1α, CXCL-1, and CXCL-8, examples of proteins known to be involved in psoriasis pathology, are associated with disease severity and whether expression patterns of these proteins on the skin surface can be used to measure pharmacodynamic effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Conversely, several studies have found that the expression of IL-1α is lower in lesional psoriatic skin than in non-lesional regions, both in adult and pediatric populations [258][259][260]. In addition, a moderate negative correlation between IL-1α and the PASI score has been observed [259]. Moreover, the level of IL-1α in the sera of psoriatic patients has been reported to be lower [261].…”
Section: Interleukin-1αmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, several studies have found that the expression of IL-1α is lower in lesional psoriatic skin than in non-lesional regions, both in adult and pediatric populations [258][259][260]. In addition, a moderate negative correlation between IL-1α and the PASI score has been observed [259]. Moreover, the level of IL-1α in the sera of psoriatic patients has been reported to be lower [261].…”
Section: Interleukin-1αmentioning
confidence: 99%
“…The abovementioned findings led Portugal-Cohen et al to identify IL-1 as a disease biomarker [257]. Conversely, several studies have found that the expression of IL-1α is lower in lesional psoriatic skin than in non-lesional regions, both in adult and pediatric populations [258][259][260]. In addition, a moderate negative correlation between IL-1α and the PASI score has been observed [259].…”
Section: Interleukin-1αmentioning
confidence: 99%
See 1 more Smart Citation